Studi Kasus Fonologis: Kesalahan Pengucapan Fonem Bahasa Indonesia pada Mahasiswa Asing di Universitas Muria Kudus - Suhaibatul Musdalifah (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
This study discusses the mispronunciation of phonemes in Indonesian by foreign students from Timor Leste at Universitas Muria Kudus (UMK). The main purpose is to identify the forms of phonological errors as well as the factors causing phoneme pronunciation errors. This research used descriptive qualitative approach method, the data were collected through listening, recording, and interview techniques. The results showed that errors mostly occurred in the change of phonemes both consonants and vowels and the addition of consonant phonemes. These pronunciation errors are influenced by differences in the phonological system between the students’ mother tongue and Indonesian. Although they do not cause changes in meaning, these errors have an impact on the fluency of communication. Therefore, more intensive teaching of phonetics and phonology is an important strategy to improve the language skills of international students.